Interview with Ashwini Deshpande: “Sticky Floors are Becoming Stickier for Women in the Indian Labor Market” - Deshpande, Ashwini (Экономическая социология, 2017)
Ashwini Deshpande, professor at the Delhi School of Economics, University of Delhi, was interviewed at the XVIII April International Academic Conference on Economic and Social Development, which took place at the Higher School of Economics on April 11–14, 2017. Deshpande gave the honorary lecture “Glass Ceiling or Sticky Floor? Gender Discrimination in Labour Markets.” The interview was prepared by Natalia Soboleva, research fellow of the Laboratory for Comparative Social Research at the Higher School of Economics. Ashwini Deshpande expressed how she became interested in labor discrimination and discussed the specificity of labor market and gender discrimination in India. Speaking about regular wage-salaried workers, she emphasized the problem of “sticky floor,” meaning higher wage gaps at the lower end of the wage distribution, which is a more acute term for developing countries than “glass ceiling.” She also pinpointed the importance of differentiating explained and unexplained components of gender discrimination and explained decomposition methods. In her work “Bad Karma or Discrimination? Male–Female Wage Gaps among Salaried Workers in India,” she demonstrated the growth of the unexplained component of gender discrimination between 1999–2000 and 2009–2010.